2011
DOI: 10.1227/neu.0b013e31821a42f3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hearing Loss After Gamma Knife Radiosurgery for Vestibular Schwannomas: Age, Cochlear Dose, and Tumor Coverage

Abstract: Older patients are more vulnerable to detrimental effects of Gamma Knife radiosurgery on hearing. We propose that cochlear dose volume histograms be created and used to reduce the percentage of the cochlear volume exposed to radiation doses greater than 5.3 Gy. This is the first report to suggest that the conformity index tumor coverage may be an important predictor of hearing outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 36 publications
0
66
0
Order By: Relevance
“…Although there is no evidence for a threshold dose below which radiation poses no threat to the cochlea, the risk of hearing loss is statistically significant with cochlea irradiation greater than 8 Gy in three sessions (dose equivalent of 5.4 Gy 3 ). Using different analytical methods, Brown et al (1) reported that, for each percentage of cochlear volume receiving at least 5.3 Gy (the mean dose in their study), there is an increase of approximately 0.168 dB in pure-tone average on follow-up audiograms.…”
Section: Cochlear Radiation and Hearing Lossmentioning
confidence: 97%
“…Although there is no evidence for a threshold dose below which radiation poses no threat to the cochlea, the risk of hearing loss is statistically significant with cochlea irradiation greater than 8 Gy in three sessions (dose equivalent of 5.4 Gy 3 ). Using different analytical methods, Brown et al (1) reported that, for each percentage of cochlear volume receiving at least 5.3 Gy (the mean dose in their study), there is an increase of approximately 0.168 dB in pure-tone average on follow-up audiograms.…”
Section: Cochlear Radiation and Hearing Lossmentioning
confidence: 97%
“…A recent study by Brown et al have also highlighted that in addition to age and cochlear dose, treatment plan conformity indices, particularly tumor coverage, are highly predictive of hearing preservation. 19 Our analysis revealed that a significantly greater number of cases were reported properly adhering to the seven of the eight elements pertinent to radiosurgery included in the Guidelines, with the exception of the nature of the tumor. The characteristic most frequently included was the size of the tumor, and the least frequently included characteristic was the nature of the tumor.…”
Section: Discussionmentioning
confidence: 87%
“…1,8,10,13,15 Kano et al 15 reported that a central cochlear dose of < 4.2 Gy was significant in patients with vestibular schwannoma retaining their hearing function. Similarly, Hasegawa et al 8 demonstrated that hearing preservation was significantly better in patients with vestibular schwannoma with a mean cochlear dose of < 6 Gy.…”
Section: Hearing Functionmentioning
confidence: 99%